2020
DOI: 10.1038/s41433-020-1069-8
|View full text |Cite
|
Sign up to set email alerts
|

Paracentral acute middle maculopathy and acute macular neuroretinopathy following SARS-CoV-2 infection

Abstract: Ophthalmic complications of COVID-19 are predicted based on prior knowledge of other coronaviruses [1]. Conjunctivitis can be the presenting sign/symptom and its presence correlates with severity [2-4]. Cotton wool spots and retinal microhaemorrhages have also been reported [5]. We report two patients who presented with a new paracentral scotoma following SARS-CoV-2 infection. Patient 1: A 37-year-old Caucasian female in week 14 of an uncomplicated pregnancy presented with a 1-day history of abrupt onset, fain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 15 publications
5
154
0
6
Order By: Relevance
“…Subtle cotton wool spots and microhemorrhages where observed in the retinal surface of four individuals, as well as hyper-reflective lesions in the ganglion cell and inner plexiform layers through optical coherence tomography (OCT) in both eyes of all patients. 2 Furthermore, Virgo and Mohamed 3 reported two patients who presented changes on OCT consistent with paracentral acute middle maculopathy and acute macular neuroretinopathy following SARS-CoV-2 infection. 3 Since Casagrande et al detected SARS-CoV-2 RNA in the retina of only 3 out of 14 patients with COVID-19 (~21%), 1 part of the retinal findings in the studies cited above 2,3 may be due to retinal SARS-CoV-2 infection, but in other patients may not.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Subtle cotton wool spots and microhemorrhages where observed in the retinal surface of four individuals, as well as hyper-reflective lesions in the ganglion cell and inner plexiform layers through optical coherence tomography (OCT) in both eyes of all patients. 2 Furthermore, Virgo and Mohamed 3 reported two patients who presented changes on OCT consistent with paracentral acute middle maculopathy and acute macular neuroretinopathy following SARS-CoV-2 infection. 3 Since Casagrande et al detected SARS-CoV-2 RNA in the retina of only 3 out of 14 patients with COVID-19 (~21%), 1 part of the retinal findings in the studies cited above 2,3 may be due to retinal SARS-CoV-2 infection, but in other patients may not.…”
Section: Dear Editormentioning
confidence: 99%
“…2 Furthermore, Virgo and Mohamed 3 reported two patients who presented changes on OCT consistent with paracentral acute middle maculopathy and acute macular neuroretinopathy following SARS-CoV-2 infection. 3 Since Casagrande et al detected SARS-CoV-2 RNA in the retina of only 3 out of 14 patients with COVID-19 (~21%), 1 part of the retinal findings in the studies cited above 2,3 may be due to retinal SARS-CoV-2 infection, but in other patients may not. There is a possibility that these findings were related to retinal lesions prior to infection associated with unreported diseases that can also damage the retina; or related to peripheral immune response triggered by SARS-CoV-2 characterized by increased levels of proinflammatory cytokines ("cytokine storm"), which can cross the blood-retinal barrier (BRB), damaging the retinal tissue.…”
Section: Dear Editormentioning
confidence: 99%
“…Es probable que durante los próximos meses veamos alguna publicación al respecto. Se han descrito también, en una carta al editor reciente, 2 casos clínicos de maculopatía aguda con escotoma paracentral en 2 pacientes confirmados con la COVID-19 48 : una mujer de 37 años con exploración oftalmológica normal en la que se vio en la TCO un área focal hiperreflectiva en las capas plexiformes con pérdida de volumen de la capa nuclear interna (maculopatía aguda paracentral); y un varón de 32 años, también con una exploración normal, con los siguientes hallazgos en la TCO: área hiperreflectiva en la capa plexiforme externa con interrupción de la banda de unión de los segmentos internos y externos de los fotorreceptores (neurorretinopatía macular aguda).…”
Section: Discussionunclassified
“…Several articles have presented evidence of ophthalmic manifestations in patients with COVID-19, with the most prevalent presentation being conjunctivitis-like symptoms. [1][2][3][4][5][6][7][8] Interestingly, some cases reported that conjunctivitis was the initial presenting symptom. 1,2 A large metaanalysis investigating the prevalence of ophthalmic disease found that in 2,228 patients diagnosed with COVID-19, 95 (4.3%) reported ocular symptoms and 21 (0.9%) presented with ophthalmic symptoms as their initial complaint.…”
Section: ■ Prevalence Of Ophthalmic Symptomsmentioning
confidence: 99%